Labor Epidural Analgesia and Autism Spectrum Disorder: Is There an Association?. Issue 2 (24th June 2022) - Wong, C.; Stevens, H.
Abstract : ( JAMA . 2021;326:1155–1157) Autism spectrum disorder (ASD) is a disorder with known genetic and environmental factors. These factors include birth complications, maternal preeclampsia, obesity, diabetes, prenatal exposure to anticonvulsants, prenatal exposure to asthma medications, and prematurity. Most researchers conclude that an increase in the diagnosis of ASD throughout the years can be attributed to the increased awareness of ASD, but some question whether factors causing or contributing to ASD are going undetected.